PERLINDUNGAN HUKUM TERHADAP KURIR PAKET DALAM JUAL BELI ONLINE DENGAN METODE PEMBAYARAN CASH ON DELIVERY (COD) - Dani Lailatul Magviro; Yasid Amali (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The purpose of this research is to find out how the law protects couriers in online buying and selling activities, especially with the Cash On Delivery (COD) payment method. The method used in this research is normative by examining library materials, namely primary, secondary and tertiary, namely legislation, books and journals. Based on this method, the research was carried out using a case approach and a statutory approach. The results of the research show that the legal protection obtained from the courier in the Cash On Delivery (COD) system payment method is to guarantee that the courier is not responsible for errors or damage to goods that are not caused by the courier's negligence or error.